PENERAPAN ASAS NEMO JUDEX IN CAUSA SUA TERHADAP KEWENANGAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA DALAM MENGUJI UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 DALAM PUTUSAN MAHKAMAH KONSTITUSI - Udak, Petrus Antonius Lela; Stefanus, Kotan Y; Tupen, Rafael R (Petitum Law Journal, 2024)
The Constitutional Court, in exercising its authority to review laws against the constitution in several of its decisions, has set aside the principle of nemo judex in causa sua, which applies universally in the legal world, thus causing conflicts of interest, one of which is Decision Number 066/PUU-II/2004. This study falls within the scope of normative legal research or library legal research. The results of this study indicate that (1) in case of conflict between the exercise of authority by the Constitutional Court and conflicting legal principles, the Constitutional Court must refer to the highest legal norms that also grant authority to the Constitutional Court, which serves as the basis for the exercise of its authority. (2) Constitutional Court Decision Number 066/PUU-II/2004 violated the principle of nemo judex in causa sua due to the unclear hierarchical position of the principle in legal science, while the basis for the Constitutional Court's duties is clear, namely referring to Article 24C paragraph (1) of the 1945 Constitution.